A daylighting field study using human feedback and simulations to test and improve recently adopted annual daylight performance metrics. Issue 5 (2nd November 2017) - Nezamdoost, Amir; Van Den Wymelenberg, Kevin
Abstract : With the latest published annual climate-based daylighting metrics and performance criteria, annual daylighting simulation has become more important to the design professions, but interpretation and application of these data are still relatively novel. This paper documents an eight-year human factors daylighting field research project using students' qualitative assessments of daylight sufficiency and corresponding point-in-time and annual climate-based daylighting simulation in a variety of commercial spaces ( n = 22) in order to provide insight to the building performance simulation community about application of these new annual daylighting metrics. The sensitivity analysis on horizontal illuminance thresholds consistently represents high correlation with students' subjective responses and annual simulation results at 250 lx, whereas point-in-time analyses produces a range of best-fitting thresholds from 200 to 300 lx for daylight sufficiency. Additionally, the study reveals that ASE 1000 lx 250 hours at 10% threshold warrants refinement, and perhaps temporal or space type sensitivity should be applied to these criteria.